Processing and evaluation of white and ricotta cheeses produced from goat milk in the Gezira State, Sudan - A. Ombabi, Yassir; E. Elimam, Mohmed (Gezira Journal of Agricultural Science, 2023)
SHORT NOTE     The demand for dairy products increased substantially in the Sudan due to improved living standards and increased urban population. However, imports of dairy products increased since domestic production is not sufficient. White cheese is the main cheese in the Sudan and the demand for exotic cheeses increased due to increased numbers of foreigners, changes in food and improved living standards. White cheese contains 47.8% total solids, 14.0% fat, 15.9% protein and 6.2% ash (Warsama et al ., 2006).Cheese is imported at high costs and it is important to produce it locally to reduce cost.